A report on the DataCite Summer 2013 Meeting. Issue 1 (2014) - ,
Abstract : Purpose – The purpose of this conference report is to highlight the key points in the DataCite Summer 2013 Meeting.Design/methodology/approach – The approach provides a summary of each presentation in the DataCite Summer Meeting.Findings – The DataCite 2013 Meeting demonstrated that there are many stakeholders engaged in the data citation and reuse mission and that much progress has been made in the past year.Originality/value – This brief summary provides highlights of the conference that are not easily gleaned from the posted online slides.